2021
DOI: 10.3390/genes12040592
|View full text |Cite
|
Sign up to set email alerts
|

Neuromesodermal Lineage Contribution to CNS Development in Invertebrate and Vertebrate Chordates

Abstract: Ascidians are invertebrate chordates and the closest living relative to vertebrates. In ascidian embryos a large part of the central nervous system arises from cells associated with mesoderm rather than ectoderm lineages. This seems at odds with the traditional view of vertebrate nervous system development which was thought to be induced from ectoderm cells, initially with anterior character and later transformed by posteriorizing signals, to generate the entire anterior-posterior axis of the central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 191 publications
(438 reference statements)
0
9
0
Order By: Relevance
“…Previous studies 19,28 have shown that b8.17 (posterior LNPCs, pLNPCs) give rise to cells near the tip of the tail of tailbud embryos. These cells are two pairs of muscle cells and four cells of posterior parts of the nerve cord and endodermal strand.…”
Section: Posterior Lnpcs Give Rise To Muscle Cells and Cells Near The...mentioning
confidence: 95%
“…Previous studies 19,28 have shown that b8.17 (posterior LNPCs, pLNPCs) give rise to cells near the tip of the tail of tailbud embryos. These cells are two pairs of muscle cells and four cells of posterior parts of the nerve cord and endodermal strand.…”
Section: Posterior Lnpcs Give Rise To Muscle Cells and Cells Near The...mentioning
confidence: 95%
“…A recent re-appraisal of urochordate embryology is a promising start for this research, as it highlighted that during gastrulation some progenitors give rise to neural and mesodermal cells in the tail. This occurs after segregation of anterior neural and mesodermal lineages [52]. As in many developmental processes, there is broader conservation, beyond chordates, of GRNs involved in axis patterning.…”
Section: Nm-research and Evo-devomentioning
confidence: 99%
“…This consists of a sensory vesicle, or brain, followed by a trunk ganglion and tail nerve cord (Fig 1A). The structure and underlying specification mechanisms of the ascidian larval CNS are well documented (reviewed in (Hudson, 2016; Hudson and Yasuo, 2021; Liu and Satou, 2020; Ryan and Meinertzhagen, 2019)). Uniquely among chordates, ascidian embryos develop with an invariant cleavage pattern and their cell lineages are well described.…”
Section: Introductionmentioning
confidence: 99%